2007
DOI: 10.1111/j.1365-2036.2007.03362.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a fermented milk containing Bifidobacterium animalis DN‐173 010 on the health‐related quality of life and symptoms in irritable bowel syndrome in adults in primary care: a multicentre, randomized, double‐blind, controlled trial

Abstract: SUMMARY BackgroundHealth-related quality of life (HRQoL) has been rarely evaluated as a primary endpoint in the assessment of the effect of probiotics on the irritable bowel syndrome (IBS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
310
1
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(340 citation statements)
references
References 61 publications
15
310
1
8
Order By: Relevance
“…53 Overall, these observations suggest that altered gut microbiota might be responsible, at least in part, for the colonic motor disturbances observed in IBS patients and might help to explain the beneficial effects observed after antibiotic or probiotic treatments. 52,55,56 In summary, the results presented here indicate that during states of dysbiosis there is a local neuro-immune adaptive response, likely associated to changes in host-bacterial interactions, which leads to functional alterations manifested as changes in viscerosensitivity and motor activity within the colon. According to previous observations, we can speculate that proliferation of C. coccoides, Lactobacillus-Enterococcus spp and Bacteroides spp.…”
Section: Discussionmentioning
confidence: 99%
“…53 Overall, these observations suggest that altered gut microbiota might be responsible, at least in part, for the colonic motor disturbances observed in IBS patients and might help to explain the beneficial effects observed after antibiotic or probiotic treatments. 52,55,56 In summary, the results presented here indicate that during states of dysbiosis there is a local neuro-immune adaptive response, likely associated to changes in host-bacterial interactions, which leads to functional alterations manifested as changes in viscerosensitivity and motor activity within the colon. According to previous observations, we can speculate that proliferation of C. coccoides, Lactobacillus-Enterococcus spp and Bacteroides spp.…”
Section: Discussionmentioning
confidence: 99%
“…104 In contrast, the number of positive to negative studies with bifidobacteria was 4:2 (including O'Mahony et al 104 ). Studies using bifidobacteria included the largest samples, 101,102 92 and Streptococcus faecium 37 need independent replication before a preliminary conclusion can be drawn.…”
Section: Global Outcomementioning
confidence: 99%
“…Studies that noted an improvement of QoL without changes in abdominal symptoms (pain, stool frequency, and bloating), 84,95,101 were labelled as "negative except QoL," since it is against all recommendations (Rome criteria and FDA/EMA) to use QoL as a primary endpoint in IBS treatment studies. Three more studies were identified as negative, contrary to the evaluation of the respective authors: one found a significant effect on abdominal pain, but not on other IBS symptoms.…”
Section: Global Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…6 Although LI is not life threatening, it does affect the quality of life and patient well-being and patients may experience extreme discomfort caused by futile treatment. 13 Clinical practice is an important facet in establishing knowledge. This was demonstrated here in that doctors who had previously encountered LI cases knew that invasive techniques are not desirable in the diagnosis of LI.…”
Section: Discussionmentioning
confidence: 99%